Neurovascular, Muscle, and Skin Changes on [18F]FDG PET/MRI in Complex Regional Pain Syndrome of the Foot: A Prospective Clinical Study. Issue 2 (29th October 2021) - Yoon, Daehyun; Xu, Yingding; Cipriano, Peter W; Alam, Israt S; Mari Aparici, Carina; Tawfik, Vivianne L; Curtin, Catherine M; Carroll, Ian R; Biswal, Sandip
Abstract: Objective: The goal of this study is to demonstrate the feasibility of simultaneous [ 18 F]-fluorodeoxyglucose (FDG) positron emission tomography (PET) and magnetic resonance imaging (MRI) for noninvasive visualization of muscular, neurovascular, and skin changes secondary to complex regional pain syndrome (CRPS). Subjects: Seven adult patients with CRPS of the foot and seven healthy adult controls participated in our [ 18 F]FDG PET/MRI study. Methods: All participants received whole-body PET/MRI scans 1 hour after the injection of 370MBq [ 18 F]FDG. Resulting PET/MRI images were reviewed by two radiologists. Metabolic and anatomic abnormalities identified, were grouped into muscular, neurovascular, and skin lesions. The [ 18 F]FDG uptake of each lesion was compared with that of corresponding areas in controls using a Mann-Whitney U -test. Results: On PET images, muscular abnormalities were found in five patients, neurovascular abnormalities in four patients, and skin abnormalities in two patients. However, on MRI images, no muscular abnormalities were detected. Neurovascular abnormalities and skin abnormalities in the affected limb were identified on MRI in one and two patients, respectively. The difference in [ 18 F]FDG uptake between the patients and the controls was significant in muscle ( P = .018) and neurovascular bundle ( P = .0005). Conclusions: The increased uptake of [ 18 F]FDG in the symptomatic areas likely reflects the increased metabolism due to the inflammatory response causing pain. Therefore, our approach combining metabolic [ 18 F]FDG PET and anatomic MR imaging may offer noninvasive monitoring of the distribution and progression of inflammatory changes associated with CRPS.